DESIGN, BUILD, AND TESTING TRANSPORTATION WHEELS FOR TRANSPORTATION OF PALM OIL FRUIT IN PEATLAND - Samosir, Rahmad; Dynasari, Melya; Pane, Medyawanti; Kristian, Yuda (International Journal of Research -GRANTHAALAYAH, 2021)
To increase the collection of oil palm yields on peatlands, the team made a design and tested the fruit vehicle using a double garden jeep. The design that is done is to make an iron wheel equipped with fins made of angled profile iron. To increase the diameter of the wheel, the standard wheels are given spokes from a 0.5 mm strip plate and are welded to the outside of the wheel with fins. The stress analysis results in the critical area show that the stress that occurs is lower than the allowable stress. The shear stress on the strip plate connected to the wheel is much less than the allowable shear stress(3 kg/cm2 ≤300 kg/cm2). Then the compressive stress that occurs is also smaller than the allowable stress (200.5 kg/cm2 ≤ 300 kg/cm2) however, the bending stress that occurs in the fins is much greater than the allowable stress (1413 kg/cm2 ≤ 400 kg/cm2), it is necessary to make additional reinforcement part fins every 10 cm. After the wheels are produced, testing is carried out by transporting 1100 kg of the palm fruit. From the results of these trials, it can be concluded that the wheel design fulfills the needs.